As estratégias de retextualização na "Entrevista da 2ª" do jornal Folha de S. Paulo - Souza, Luciane Cristina Del Ben de (2007)
The present work aims at poiting out some linguistic/discursive strategies used by written press journalists when rendering an oral interview into a written one, in order to verify at which level such strategies may be instrument of manipulation of ideas. With this purpose we have used as a theoretical support the studies developed by Marcuschi (2004) regarding the relationship between orality/writing, following, in part, the model of textual-discursive operations proposed by the author, and Gomes studies (1995). Concerning the changes resultant from transforming direct into reported speech, we used the observations by theorists such as: Authier-Revuz (2001) and Maingueneau (1997, 2004), among others. The object of analysis of this study was an interview conceded by the historian Luiz Felipe de Alencastro in September 2005, to the newspaper Folha de S. Paulo. The results obtained sustain that the strategies used by the newspaper in the transformation of the transcribed matter into the published text produce significant changes in the meaning of statements, compromising thus, the essence of the original text, and such strategies become efficient resources of news manipulation